Nutrient management on the growth and yield of black cumin (Nigella sativa L.) (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was carried out at the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, during rabi (winter) season of 2016-17 to evaluate the effects of fertilizer treatments on black cumin (BARI Kalozira-1). The field belongs to Shallow red-brown terrace soil of Salna series under AEZ-28 (Madhupur Tract). The experiment was laid out in randomized complete block design (RCBD) with three replications. Results showed that the application of nutrient elements had positive effect on plant height, branches per plant, capsule setting, umbels per plant, capsules per plant, capsule size, seeds per capsule, 1000-seed weight and seed yield of black cumin. The highest seed yield (1277 kg ha-1) was obtained from 75% RDCF + 25% cowdung-N treatment followed by 100% RDCF (N80P45K50S20Zn5B2 kg ha-1) and the lowest seed yield (420 kg ha-1) was recorded with 50% RDCF. Thus, the IPNS treatment 75% RDCF + 25% cowdung-N appeared to be the best suitable package for black cumin cultivation in this location.Bangladesh J. Agril. Res. 43(2): 205-210, June 2018